Biogenic Selenium Nanoparticles: Anticancer, Antimicrobial, Insecticidal Properties and Their Impact on Soybean (Glycine max L.) Seed Germination and Seedling Growth - Asmaa Abdelsalam; Heba El-Sayed; Heba M. Hamama; Mostafa Y. Morad; Abeer S. Aloufi; Rehab M. Abd El-Hameed (Biology, 2023)
Selenium nanoparticles (SeNPs) have demonstrated significant potential in a variety of disciplines, making them an extremely desirable subject of research. This study investigated the anticancer and antibacterial properties of my-co-fabricated selenium SeNPs, as well as their effects on soybean (Glycine max L.) seeds, seedling growth, cotton leafworm (Spodoptera littoralis) combat, and plant pathogenic fungi inhibition. SeNPs showed anticancer activity with an IC50 value of 1.95 µg/mL against MCF-7 breast adenocarcinoma cells. The myco-synthesized SeNPs exhibited an antibacterial effect against Proteus mirabilis and Klebsiella pneumoniae at 20 mg/mL. The use of 1 µM SeNPs improved soybean seed germination (93%), germination energy (76.5%), germination rate (19.0), and mean germination time (4.3 days). At 0.5 and 1.0 µM SeNPs, the growth parameters of seedlings improved. SeNPs increased the 4th instar larval mortality of cotton leafworm compared to control, with a median lethal concentration of 23.08 mg/mL. They inhibited the growth of Fusarium oxysporum, Rhizoctonia solani, and Fusarium solani. These findings demonstrate that biogenic SeNPs represent a promising approach to achieving sustainable progress in the fields of agriculture, cancer therapy, and infection control.